2009
DOI: 10.4103/0255-0857.55437
|View full text |Cite
|
Sign up to set email alerts
|

Review of Virulence Factors of Enterococcus: An Emerging Nosocomial Pathogen

Abstract: not only in the treatment of enterococcal infections but also because the organism can horizontally transfer this resistant determinant to other Vancomycin-susceptible species. [6] Until recent times, the VRE strains were found sensitive to Linezolid. Resistance to Linezolid is slowly developing, posing several questions on the virulence factors and their survival mechanisms. [7] This review article focuses on the development of virulence factors of the organism and their signiÞ cance in survival of the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 47 publications
0
82
1
Order By: Relevance
“…10 Our prospective study was carried out on 100 Enterococcal isolates, during a 20 months period from May 2015 to December 2016at Aarupadai Veedu medical college and hospital. The predominant species isolated in this study were E.faecalis constituting 81% of isolates followed by 19% of E. faecium.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our prospective study was carried out on 100 Enterococcal isolates, during a 20 months period from May 2015 to December 2016at Aarupadai Veedu medical college and hospital. The predominant species isolated in this study were E.faecalis constituting 81% of isolates followed by 19% of E. faecium.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Enterococci are important because of their role as the leading cause of nosocomial infections which have a significant role in dissemination and persistence of drug resistance genes. 3 Vancomycin is a member of a class of antibiotics referred to as glycopeptides therefore vancomycin resistant enterococci (VRE) can also be referred to as Glycopeptide resistant enterococci (GRE).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 39 (43.8%) isolates of E. faecalis and 2 (18.18%) isolates of E. faecium were producing gelatinase. A study from India by Upadhyaya et al, in the year 2009, reported that 39% clinical isolates were producing gelatinase [10]. Another study by Strzelecki et al from Poland reported that, of 153 E. faecalis, 53% of strains producing gelatinase, and among these, isolates from CSF were commonly producing gelatinase (75%) followed by isolates from urine (71%) less frequently by isolates from wound and blood.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 42 (47.19%) isolates of E. faecalis and 4 (36.36%) isolates of E. faecium were producing biofilm, respectively. Upadhyaya et al from India reported that 32% of clinical isolates were producing biofilm, but only 16% of commensal isolates were producing biofilm [10]. The worldwide biofilm producing prevalence was varied from each other country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation